AN ANALYSIS OF CHILDHOOD GOOD VALUES IN C.S.LEWIS’S NOVEL THE VOYAGE OF THE DAWN TREADER - Panisia Julita; Mukhrizal .; Indah Damayanti (Journal of English Education and Teaching, 2018)
This research aimed to find out childhood good values in C.S. Lewis’s Novel The Voyage of the Dawn Treader and their implications for education. The research was carried out by employing a descriptive qualitative method of library research. The data were collected by reading and analyzing the novel thoroughly. The results of the study revealed that there were several childhood good values in The Voyage of the Dawn Treader novel such as obedience, honesty, imagination, pleasure, kinship, bravery, regret, intelligence, helpfulness, forgiveness, and friendship. Nevertheless, there were also some bad values namely annoyance, selfishness, and greediness. The good values in the novel were basically universal, so they were congruent with the 2013 Curriculum in term of spiritual and social competencies. Thus, they implied that they can be used as teaching materials and source of references to teach both competencies